2016
DOI: 10.23887/jptk-undiksha.v13i2.8527
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul Berbasis Project Based Learning Pada Mata Pelajaran Pemrograman Web Kelas X Di SMK Negeri 3 Singaraja

Abstract: AbstrakPenelitian ini bertujuan (1) Untuk merancang dan mengimplementasikan Pengembangan E-modul Berbasis Project Based Learningpada Mata Pelajaran Pemrograman Web Kelas X  di SMK Negeri 3 Singaraja. (2)Untuk mengetahui respon siswa dan guru terhadap Pengembangan E-modul Berbasis Project Based Learningpada Mata Pelajaran Pemrograman Web Kelas X  di SMK Negeri 3 Singaraja.Metode penelitian yang digunakan dalam penelitian ini adalah penelitian dan pengembangan. dengan model pengembangan ADDIE. Subjek penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The results of this study are supported by research (Budiningarti et al, 2015;Sumarmi, 2012;Sumarmi̇ et al, 2020;Utami et al, 2016;Winaya et al, 2016) that assigning or International Journal of Instruction, October 2021 • Vol.14, No.4 providing a project-based learning module was very useful because researchers and students could focus on the project implementation. It is also supported by research (Budiningarti et al, 2015) that students' skills in developing learning media by using problem-based learning models were in the range of 77.94-97.06 of 0-100 scale with an average of 87.04 which means good.…”
Section: The Effect Of Using E-module With Blended Learning On Student Innovation In Designing Learning Mediasupporting
confidence: 70%
“…The results of this study are supported by research (Budiningarti et al, 2015;Sumarmi, 2012;Sumarmi̇ et al, 2020;Utami et al, 2016;Winaya et al, 2016) that assigning or International Journal of Instruction, October 2021 • Vol.14, No.4 providing a project-based learning module was very useful because researchers and students could focus on the project implementation. It is also supported by research (Budiningarti et al, 2015) that students' skills in developing learning media by using problem-based learning models were in the range of 77.94-97.06 of 0-100 scale with an average of 87.04 which means good.…”
Section: The Effect Of Using E-module With Blended Learning On Student Innovation In Designing Learning Mediasupporting
confidence: 70%
“…A digital module is a learning tool designed to achieve certain competencies in which it contains material, methods, restrictions and how to conduct the process of conducting the learning outcomes structured and presented with Utilizing communication technology and information in the form of interned and electronic devices [18]. In addition, digital modules are teaching material based on information communication technology that has various advantages, among others; Operation of the generated modules can be done easily by the user, modules can be equipped with background music, video, slide show, can be learned online and offline, learning evaluation can be made using the application quiz qreator, can be opened via a computer or a smarphone, this module can be used as a learning resource for students who want to learn without time limitation [19].…”
Section: Digital Module (E-module)mentioning
confidence: 99%
“…The results of the questionnaire showed that there were still more than 40% of educators who have not made digital material. Even though, digital learning materials are the most effective part of online learning [14][15]23]. So, it is recommended for educators to make creative and innovative digital materials.…”
Section: Based Onmentioning
confidence: 99%